Variability and host specificity of witchweed [Striga hermonthica (Del.) Benth.] populations on millet [Pennisetum glaucum (L.) R. Br.] - Dafaallah, Awadallah B; Babike, Abd Elgabar T; Zain El Abdeen, Mohammed H (Gezira Journal of Agricultural Science, 2014)
Field surveys and greenhouse experiments were conducted during season 2009/10 in the Sudan to investigate variability and host specificity of witchweed [ Striga hermonthica (Del.) Benth.] populations. Field surveys were conducted in S. hermonthica endemic areas in Gadarif, Gezira and Kordofan to collect seeds from Striga plants growing under their respective hosts. A total of fifteen S . hermonthica populations were collected. Twelve S . hermonthica populations, one each, were collected from under sorghum and three S . hermonthica populations, one each, were collected from under millet. A greenhouse experiment was undertaken at the horticulture nursery, Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, to test the infectivity of seeds of witchweed populations on millet, cultivar Ashana, which is known for its differential response and to study virulence of parasitism on this cultivar. The fifteen S. hermonthica populations were arranged in a randomized complete block design with three replicates. Growth and harvest attributes on the parasite and crop were measured. Data were collected and transformed as necessary to √x+0.5 and subjected to the analysis of variance procedure. Means were separated for significance using Duncan's Multiple Range Test (at p £ 0.5). The greenhouse experiment showed that emergent S. hermonthica , capsules per plant and shoot dry weight were highest on the respective host. It is noteworthy that some of the Striga , sorghum populations, displayed limited emergence on millet and produced seeds. S. hermonthica populations significantly reduced growth and yield of millet. However, the magnitude of the damage attained, by each   population was highest on the respective host. These findings suggest the existence of inter-crop specialization. Moreover, the results confirmed the existence of two strains of S. hermonthica , one specific to sorghum and the other to millet. These findings showed clearly the complexity of obtaining millet cultivars with high and durable resistance across locations.      طفيل البُودا Striga hermonthica (Del.)، نبات متطفل إجبارياً على الجذور ينتمي للعائلة الهالوكية (Orobanchaceae)، يُهاجم محاصيل الغلال المهمة في أفريقيا. أدى وجود السلالات الفسيولوجية، التباينات الايكولوجية وعزلات الطفيل بالإضافة للتباين في حجم مخزون التربة من البذور، إلى عقبات جدية لتطوير وسائل تحكم بسيطة وفعالة. لذا أُجريت مسوحات حقلية وتجارب بيوت محمية خلال الموسم 2009/ 2010 في السودان لبحث التباين وتخصصية العائل في البُودا. المسوحات الحقلية أجريت في المناطق الموبؤة بالبُودا في القضارف والجزيرة وكردفان، لجمع البذور من نباتات البُودا النامية على عوائلها الخاصة. جمعت اثني عشر عشيرة للبُودا، واحدة لكل، من تحت الذرة الرفيعة، وجمعت ثلاث عشائر من تحت الدخن، واحدة لكل. أجريت تجربة البيوت المحمية بمشتل البساتين، كلية العلوم الزراعية، جامعة الجزيرة، ود مدني، السودان، لاختبار تلويث بذور عشائر البودا للدخن، الصنف عشانا، المعروف باستجابته التفضيلية، ولدراسة التباين في التطفل على هذا الصنف. وُضعت الخمسة عشر عشيرة للبُودا في تصميم قطاعات عشوائية كاملة بثلاث تكرارات. تم تحديد مقاييس النمو والحصاد بالنسبة للطفيل والمحصول. حُولت البيانات عند الضرورة (√x+0.5) وأُخضعت لتحليل التباين. تمت مقارنة المتوسطات بواسطة اختبار دنكن، عندما كان الاختبار معنويا. أوضحت نتائج تجارب البيوت المحمية أن قمة انبثاق نباتات البُودا في الأصيص، الكبسولات في النبات، الوزن الجاف للمجموع الخضري، عدد نباتات البُودا تحت سطح التربة في الأصيص والعدد الكلى لنباتات البُودا في الأصيص كانت أعلى على عوائلها الخاصة. الجدير بالملاحظة أن بعض نباتات البُودا، عشائر الذرة الرفيعة، أظهرت بزوغاً محدوداً على الدخن وأنتجت بذوراً. خفضت عشائر البُودا معنوياً نمو وإنتاج الذُرة والدُخن. ولكن تحققت أعلى مستويات الضرر لكل عشيرة من البُودا على عائلها الخاص. أوضحت نتائج هذا البحث وجود التخصصية بين وداخل نوع المحصول. كما أن النتائج تؤكد وجود سلالتان للبُودا واحدة متخصصة في الذُرة الرفيعة والأخرى في الدُخن. أظهرت هذه النتائج بوضوح التعقيد في الحصول على أصناف من الدخن ذات مقاومة عالية وعريضة في المناطق المختلفة.